A Meaning-Aware Cultural Tourism Intelligent Navigation System Based on Anticipatory Calculation - Meng, Lei; Liu, Yuan (Frontiers in Psychology, 2021)
In order to improve the personalized service of cultural tourism, anticipatory calculation has become an essential technology in the content design of intelligence navigation system. Culture tourism, as a form of leisure activity, is being favored by an increasing number of people, which calls for further improvements in the cultural consumption experience. An important component of cultural tourism is for tourists to experience intangible cultural heritage projects with local characteristics. However, from the perspective of user needs and the content adaptive system, there are few suitable intelligent navigation and user demand anticipatory systems for intangible cultural heritage content. Purple clay culture is one of the first batches of national intangible cultural heritage protection projects in China. Therefore, taking purple clay culture exhibition as an example, this paper attempts to analyze the personalized information demand of tourism consumption experience in intangible cultural heritage communication activities with affective computing and meaning-driven innovative design method, by taking the content design in the navigation system as the research object. This paper uses the theory of planned behavior to calculates the relationship between tourists’ attitude, experience behavior, and display information demand. The findings indicate two issues. First, tourists’ demand for the entertainment and leisure attributes of intangible cultural heritage is greater than the demand for educational function attributes. Second, the meaning elements of information can change tourists’ beliefs in intangible cultural heritage and affect their attitude and behavior towards such heritage. According to the research results, strengthening the meaning elements of specific group information can improve people’s cultural identity and tourism satisfaction. The research results provide the basis for the content design direction of future museum intelligent navigation systems.